1994
DOI: 10.1177/027836499401300107
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Visual Servoing Using Controlled Illumination

Abstract: A real-time visual servoing approach is applied to robotics tasks consisting of the positioning of the end effector with respect to a priori known polyhedral objects. The vision apparatus is constituted by a compact CCD camera rigidly coupled with two laser stripes mounted on the wrist of a robot manipulator. The objective is to servo the robot end effector at a constant position and orientation with respect to a known object in three-dimensional space in the field of view of the sensory system. The approach i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The paper [48] by Urban et al is one of the earliest works using TLVS to go beyond heuristic approaches and adopt the modern IBVS framework. This pioneering work derives several interaction matrices for feature sets generated by projected laser planes and points on polygonal objects.…”
Section: Existing Textureless Visual Servoing Applications Addressing...mentioning
confidence: 99%
See 1 more Smart Citation
“…The paper [48] by Urban et al is one of the earliest works using TLVS to go beyond heuristic approaches and adopt the modern IBVS framework. This pioneering work derives several interaction matrices for feature sets generated by projected laser planes and points on polygonal objects.…”
Section: Existing Textureless Visual Servoing Applications Addressing...mentioning
confidence: 99%
“…Experimental work in the paper demonstrated that a robot could be positioned above a car battery using two projected laser planes and a purely IBVS control law, as shown in Figure 6. (Source: [48])…”
Section: Existing Textureless Visual Servoing Applications Addressing...mentioning
confidence: 99%
“…As far as L ωX is concerned (20) and,ṅn − nṅ being an anti-symmetric matrix, it can be demonstrated thaṫ…”
Section: A Definition Of the Interaction Matrix And Of The Control Lawmentioning
confidence: 99%
“…The planar object can be also modeled by using the following minimal equation: (6) with (7) The laser pointer can be modeled according to a vectorial equation as follows: (8) is the laser origin defined as the intersection of the laser direction with the plane , and is the distance from to . The interaction matrix of a normalized image point corresponding to the 3-D intersection of a laser pointer and a planar object is [21], [22] (9) with (10) A nonminimal representation for this matrix can be found in [3]. Note that the rank of is 1.…”
Section: A Laser Pointer Modelingmentioning
confidence: 99%
“…However, there are few visual servoing works exploiting structured light. The main contribution in this field is due to Motyl et al [3], [4], who modeled the kinematics of simple visual features obtained when projecting laser planes onto planar objects and spheres. Andreff et al [5] used a laser pointer in their approach based on 3-D lines in order to control the depth.…”
mentioning
confidence: 99%